2017
DOI: 10.1038/ncomms13878
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of CMOS optical parametric amplifiers with USRN:Si7N3 above the two-photon absorption edge

Abstract: CMOS platforms operating at the telecommunications wavelength either reside within the highly dissipative two-photon regime in silicon-based optical devices, or possess small nonlinearities. Bandgap engineering of non-stoichiometric silicon nitride using state-of-the-art fabrication techniques has led to our development of USRN (ultra-silicon-rich nitride) in the form of Si7N3, that possesses a high Kerr nonlinearity (2.8 × 10−13 cm2 W−1), an order of magnitude larger than that in stoichiometric silicon nitrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
97
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(111 citation statements)
references
References 64 publications
0
97
4
Order By: Relevance
“…Increasing the relative content of silicon vs nitride yields a silicon-rich nitride film [17]. This is highly relevant for nonlinear optics applications because waveguides fabricated from silicon rich nitride tend to have a higher nonlinear Kerr coefficient [20][21][22]. Lacava et al recently demonstrated that the Kerr coefficient can be enhanced by an order of magnitude in silicon nitride waveguides fabricated via plasma-enhanced chemical vapor deposition (PECVD) by varying the silicon content of the film [21].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the relative content of silicon vs nitride yields a silicon-rich nitride film [17]. This is highly relevant for nonlinear optics applications because waveguides fabricated from silicon rich nitride tend to have a higher nonlinear Kerr coefficient [20][21][22]. Lacava et al recently demonstrated that the Kerr coefficient can be enhanced by an order of magnitude in silicon nitride waveguides fabricated via plasma-enhanced chemical vapor deposition (PECVD) by varying the silicon content of the film [21].…”
Section: Introductionmentioning
confidence: 99%
“…Applying different pumping schemes, FWM in an integrated platform have been demonstrated for providing various applications, such as signal regeneration [1], wavelength channel conversion [2], and logic operations [3], all of which could be modulation-format transparent and compatible with coherent communications. The quest for all-optical components has naturally targeted materials with extremely large nonlinearity including semiconductors (Si, III-V) [4][5][6], chalcogenide glasses [7] and polymers [8], but also low-loss platforms (silicon dioxide [9] and silicon nitride [10,11]). A lot of efforts have been made to develop nonlinear photonic devices on the silicon platform; even though promising results have been shown, this platform suffers from free-carrier dispersion and absorption through two-photon absorption (TPA) process which leads to a limitation of the operational speed of devices.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the strong two-photon absorption (TPA) of silicon at near-infrared wavelengths poses a fundamental limitation to the performance of nonlinear photonic devices in the telecommunications band [5,6]. Other CMOS compatible platforms such as silicon nitride [19,20], high index doped silica glass [21,22], and silicon rich nitride [23,24], have a much weaker TPA and a higher nonlinear figure of merit (FOM), although they still face limitations in terms of nonlinear efficiency due to their lower intrinsic Kerr nonlinearity [5,25].…”
Section: Introductionmentioning
confidence: 99%